Enhancing the community college pathway to engineering careers - Mattis, Mary C.; Sislin, John, 1965- (National Academies Press, 2005)
Annotation Community colleges play an important role in starting students on the road to engineering careers, but students often face obstacles in transferring to four-year educational institutions to continue their education. Enhancing the Community College Pathway to Engineering Careers, a new book from the National Academy of Engineering and the National Research Council, discusses ways to improve the transfer experience for students at community colleges and offers strategies to enhance partnerships between those colleges and four-year engineering schools to help students transfer more smoothly. In particular, the book focuses on challenges and opportunities for improving transfer between community colleges and four-year educational institutions, recruitment and retention of students interested in engineering, the curricular content and quality of engineering programs, opportunities for community colleges to increase diversity in the engineering workforce, and a review of sources of information on community college and transfer students. It includes a number of current policies, practices, and programs involving community college-four-year institution partnerships.
Keywords: Engineering -- Study and teaching (Higher) -- United States.; Community colleges -- Curricula -- United States.; Engineering -- Vocational guidance -- United States.; Collèges communautaires -- Programmes d'études -- États-Unis.; Ingénierie -- Orientation professionnelle -- États-Unis.; TECHNOLOGY & ENGINEERING -- Engineering (General); TECHNOLOGY & ENGINEERING -- Reference.; Community colleges -- Curricula; Engineering -- Study and teaching (Higher); Engineering -- Vocational guidance; United States